2005
DOI: 10.1242/jeb.01754
|View full text |Cite
|
Sign up to set email alerts
|

Three calpains and ecdysone receptor in the land crabGecarcinus lateralis: sequences, expression and effects of elevated ecdysteroid induced by eyestalk ablation

Abstract: SUMMARY Crustacean muscle has four calpain-like proteinase activities (CDP I, IIa,IIb and III) that are involved in molt-induced claw muscle atrophy, as they degrade myofibrillar proteins in vitro and in situ. Using PCR cloning techniques, three full-length calpain cDNAs (Gl-CalpB, Gl-CalpM and Gl-CalpT) were isolated from limb regenerates of the tropical land crab Gecarcinus lateralis. All three had highly conserved catalytic (dII)and C2-like (dIII) domains. Gl-CalpB was classified as a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 76 publications
4
41
1
Order By: Relevance
“…In crustaceans, it is generally known that ecdysteroids are first synthesized in the Y-organ (molting gland), and subsequently released into hemolymph where they are hydroxylated to become 20-hydroxyecdysone (20E), a biologically active formwhich belongs to the nuclear receptor family, to activate DNA regulatory element (Bortolin et al 2011, Gaertner et al 2012. In crustaceans, EcR can form a heterodimer with another nuclear receptor known as retinoid X receptor (RXR), which is orthologous with ultraspiracle (USP) in insects, to regulate the downstream genes in the ecdysteroid signaling pathway (Wu et al 2004, Kim et al 2005a,b, Hopkins et al 2008, Hill et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In crustaceans, it is generally known that ecdysteroids are first synthesized in the Y-organ (molting gland), and subsequently released into hemolymph where they are hydroxylated to become 20-hydroxyecdysone (20E), a biologically active formwhich belongs to the nuclear receptor family, to activate DNA regulatory element (Bortolin et al 2011, Gaertner et al 2012. In crustaceans, EcR can form a heterodimer with another nuclear receptor known as retinoid X receptor (RXR), which is orthologous with ultraspiracle (USP) in insects, to regulate the downstream genes in the ecdysteroid signaling pathway (Wu et al 2004, Kim et al 2005a,b, Hopkins et al 2008, Hill et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with U. pugilator also suggested temporal-and organ/tissue-specific distribution of several EcR isoforms (Durica et al 2002). It may be deduced that various EcRs control specific responses in different organs and determine thus tissue sensitivity to ecdysteroids (Kim et al 2005a;Zou 2005).…”
Section: Role Of Classical Endocrine Glands In Reproductionmentioning
confidence: 97%
“…EcR belongs to a nuclear receptor family (receptors acting as transcription factors), and it has a typical gene composition of five domains from which DNA-binding domain (DBD) and ligand-binding domain (LBD) are phylogenetically conserved. Analyses of these two domains in Uca pugilator (Durica et al 2002) and Gecarcinus lateralis Freminville, 1835 (Kim et al 2005a) revealed high similarity to EcR from insects. Recent studies with U. pugilator also suggested temporal-and organ/tissue-specific distribution of several EcR isoforms (Durica et al 2002).…”
Section: Role Of Classical Endocrine Glands In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al, 2005). Pemrick and Grebenau reported that proteolytic activity by calcium-activated neutral protease (CANP; also known as calpain) in the head region of ~200·kDa MHC from rabbit muscle produced 180, 165 and 150·kDa sized MHC peptides (Pemrick and Grebenau, 1984).…”
Section: Identification Of a Mhc Degradation Productmentioning
confidence: 99%